PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS KETERAMPILAN PROSES SAINS PADA KOMPETENSI DASAR MENYELIDIKI SIFAT-SIFAT ZAT - Meita Widian Pangestika; Eko Suyanto; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
According to the writer’s observation in the school by using interview with the students and science teacher in the SMPN Bina Bhakti Way Pangubuan, it is given that the teacher has not use the school facilities maximally such as teaching laboratory. In the basic competence states of matter, students can not receivethat material clearly, exactly in investigate the physical properties based on its states and its application in the students’ daily life. Considering these problems, therefore the writer develops the worksheet as a learning media. The worksheet is developed based on KPS. KPS is the directly investigate by students thatcontains the questions (doing and predicting observation, rouping, predicting, communicating, and hypothesizing an event), the activity of science ability process (pre-laboratory and laboratory activity), summarizing, doing the exercises, and evaluating. There is a key answer of this worksheet. The designconsists of seven steps development procedure and product test, they are:analysis necessity, identification resources to meet a need, identificationspecifications intended products users, product development, test internal proper test products, test external test expedience products by users and the laststage production. The result of internal test shows that the media has been developed satisfies theory criteria and fit for use as one of the media of learning. The result of external test shows that the quality of this media is very interesting, very easy to use, and very useful and effective to use as a learningmedia. It can be seen from the students’ enthusiastic and the students’ ability to answer worksheet’s questions. So, we can conclude this worksheet learning media based KPS has been tested and proper to use with the quality is very interesting, very easy to use, and very useful, and it is called effective as alearning media. Keywords: Worksheet Students Based Skill Process Science